Characterization of the complete plastid genome sequence of Allium Fasciculatum - Hao Li; Deng-Feng Xie; Song-Dong Zhou; Xing-Jin He (Mitochondrial DNA. Part B. Resources, 2019)
Allium fasciculatum is an endemic alpine species of Allium L., which is confined to the Qinghai-Tibet Plateau, China. In this study, we sequenced the complete plastid genome of A. fasciculatum and firstly reported it. A typical quadripartite structure was detected with 152,931 bp in length and it consists of a pair of inverted repeats with 26,464 bp, separated by small and large single copies with 17,838 bp and 82,167 bp, respectively. The genome contained 132 genes, consisted of 85 coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analyses based on the whole complete genome sequences showed A. fasciculatum was closely clustered with A. paradoxum and Allium ursinum with high support.